1974
DOI: 10.1111/j.1570-7458.1974.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL ACTIVITIES OF SAPONIN COMPONENTS FROM DUPUITS AND LAHONTAN ALFALFA1

Abstract: Saponins of DuPuits and Lahontan alfalfa cultivars were extracted and fractionated by preparative thin‐layer chromatography. The ten relatively well‐defined saponin fractions obtained from each cultivar were chemically characterized by major aglycone and carbohydrate moieties. Lahontan contained considerably more soyasapogenol A than DuPuits, but medicagenic acid predominated in DuPuits. The near absence of medicagenic acid from Lahontan fractions was the most significant difference in composition of Lahontan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Cloversaponin I-V methyl ester Soyasaponin I Soyasaponin I methyl ester Soyasaponin II methyl ester Azukisaponin II methyl ester Astragaloside VIII Toxic to fungi (Wolters, 1968), insects (Horber et al, 1974), molluscs (Agarwal and Rastogi, 1974;Mølgaard et al, 2000) and ruminants (Agarwal and Rastogi, 1974). Health-promoting activities (Rao and Gurfinkel, 2000).…”
Section: Saponinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloversaponin I-V methyl ester Soyasaponin I Soyasaponin I methyl ester Soyasaponin II methyl ester Azukisaponin II methyl ester Astragaloside VIII Toxic to fungi (Wolters, 1968), insects (Horber et al, 1974), molluscs (Agarwal and Rastogi, 1974;Mølgaard et al, 2000) and ruminants (Agarwal and Rastogi, 1974). Health-promoting activities (Rao and Gurfinkel, 2000).…”
Section: Saponinsmentioning
confidence: 99%
“…Saponins are toxic to fungi (Wolters, 1968), insects (Horber et al, 1974;Adel et al, 2000), molluscs (Agarwal and Rastogi, 1974;Mølgaard et al, 2000), nematodes (Argentieri et al, 2007) and ruminants (Agarwal and Rastogi, 1974), but can have health-promoting activities (Rao and Gurfinkel, 2000). Soyasaponin I is toxic to the plant-parasitic nematode Xiphinema index (Argentieri et al, 2007), causes prolongation of the larval and pupal stages, retards growth, increase mortality, and reduce fecundity and fertility of the insect Spodoptera littoralis (Adel et al, 2000), but stimulates the growth of wheat (Triticum aestivum L.) (Oleszek, 1993).…”
Section: Biological Effects Of Saponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandabe (2002), using thin layer chromatography, detected two types of saponins. Zimmer et al (1967) reported selective toxicity of saponins on microorganisms, indicating that not all saponins do affect the growth of microorganisms and individual saponins might be responsible for the differences in the growth inhibitory activities (Horber et al, 1974). The natives may be using the plant for wound dressing not because of its antibacterial action but probably because of the presence of tannins in the extract.…”
Section: Resultsmentioning
confidence: 98%
“…Les recherches ont également mis en œuvre des milieux holidiques reproduisant la composition de cette sève . Les (Bournoville, 1993) (Horber et al, 1974 ;Krzymanska et Waligora, 1986 (Bournoville, 1993), à savoir que la résistance des génotypes de luzerne vis-à-vis du puceron du pois n'apparaît pas liée à ce composé. En utilisant d'autres plantes de luzerne, nous avons récemment montré (Girousse et Bournoville, 1994) …”
Section: Introductionunclassified